Keseimbangan Dasar Sungai Pada Belokan Sedang (Ii) Dengan Uji Model Fisik Krib Permeabel Ban Mobil Bekas - I Made Udiana (JUTEKS : Jurnal Teknik Sipil, 2020)
This research is aimed at analyzing the slope is average in a model of river bed, the slope of each section and the maximum depth of the degradation which result from the construction of permeable on the model for the river that is using moderate bends (II), of minimum discharge , average discharge and maximum discharge, in order to determine the proper course of water flow, so as to achieve balance in river beds. The scour area of the permeable groyne formation is perpendicular to the scour I (ATLG I) = 0,4800 m2 with benchmarks ATLG I < SeDKP and scour II(ATLG II) = 0,6000 m with benhmarks ATLG II < SeDKP and the average slope of the river bed that occurs and the average slope of the river bed that occurs (Ids TL) = 0,0097 with benchmarks IdsTL < SeDKP so that the balance of the river bed is achieved and the hypothesis is accepted